The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1017/s0950268822000681
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hepatitis B surface antigen carrier status and pregnancy outcome: a retrospective cohort study

Abstract: To investigate the effect of maternal hepatitis B surface antigen (HBsAg) carrier status during pregnancy on pregnancy outcomes in a population of patients in Hangzhou, China. A retrospective cohort study was conducted to analyse data from 20 753 pregnant women who delivered at Hangzhou Women's Hospital between January 2015 and March 2020. Of these, 18 693 were normal pregnant women (the non-exposed group) and 735 were HBsAg carriers (the exposed group). We then analysed by binary multivariate logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The study also found no association between preterm delivery, premature rupture of membranes, cesarean section, meconium-stained amniotic fluidis and HBV infection, consistent with studies ( 7 , 9 , 33 , 34 ). Interestingly, it has been shown in some studies ( 35–37 ) that maternal HBsAg carriers may have an increased risk of preterm birth.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The study also found no association between preterm delivery, premature rupture of membranes, cesarean section, meconium-stained amniotic fluidis and HBV infection, consistent with studies ( 7 , 9 , 33 , 34 ). Interestingly, it has been shown in some studies ( 35–37 ) that maternal HBsAg carriers may have an increased risk of preterm birth.…”
Section: Discussionsupporting
confidence: 89%
“…In this field, there are few reports on the association between HBsAg carriers and pregnancy complications and the relationship between them is unclear. Chen et al reported that HBsAg-positive pregnant women have an increasing risk of intrahepatic cholestasis of pregnancy (ICP), low birth weight, fallopian cysts, cesarean scar pregnancy, thrombocytopenia, and fetal distress ( 7 ). Wan et al found that maternal HBsAg carrying was associated with increasing risk of pregnancy-induced hypertension, fetal distress, cesarean delivery and macrosomia ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Cai et al [ 26 ] showed that chronic HBV infection during pregnancy may increase ICP (aOR = 1.700) and that pregnant women with an HBeAg-positive (aOR = 2.960) or HBeAg-negative (aOR = 1.520) status still have the risk of ICP. Our previous study also found that HBsAg-positive pregnant women in Hangzhou, China have a higher risk of ICP (aOR = 3.169) [ 19 ]. These studies demonstrated that pregnant women who were carriers of hepatitis B were more likely to develop ICP.…”
Section: Discussionmentioning
confidence: 95%
“…Univariate analysis of qualitative or quantitative data was performed using the Chi-Squared test or Mann–Whitney U test, with P < 0.10 as the selection criteria for multivariate binary logistic regression analysis. Multivariate binary logistic regression analysis was used to screen the variable odds ratio (OR) and 95% confidence interval (CI) of each relevant influencing factor, adjusted odds ratio (aOR), after adjusting for potential confounding variables (Backward: Likelihood Ratio Test (LR): Based on all candidate variables, the independent variables that do not meet the requirements of the significant retention level are eliminated from the model at one time, and the remaining variables are entered into the model [ 19 ]). The variable input in step 1 included: before the occurrence of ICP: gravidity ≥ 1, parity ≥ 1, hypertensive disorders of pregnancy (HDP) [gestational hypertension (GH), preeclampsia (PE)], hyperlipidemia, gestational diabetes mellitus (GDM), anemia, thrombocytopenia, hepatitis B virus carriers, BMI (Categories); after the occurrence of ICP: premature rupture of membranes (PPROM), fetal growth retardation, preterm birth, gestational days (Categories), caesarean section, infant sex (female), infant length (cm), infant weight (Categories).…”
Section: Methodsmentioning
confidence: 99%
“…Hepatitis B virus (HBV) carrier status was defined as the hepatitis B surface antigen (HBsAg) seropositive on serological testing, 1 which is a major public health problem around the world. It has a high risk of death from hepatic diseases, such as cirrhosis and hepatocellular cancer.…”
Section: Introductionmentioning
confidence: 99%